The effect of combined hurdle and leader drills on dolyo chagi kick speed in taekwondo - Persada, Tahta Syam Utama; Kahri, Ma’ruful; Mashud, Mashud; Fadillah, Muhammad; Yandi, Pebri (Jurnal Ilmu Keolahragaan, 2025)
Background. This research highlights the importance of the speed of the Dolyo Chagi kick in Taekwondo, which plays a role in scoring points during matches. Many junior athletes struggle to improve their kicking speed, so a combination of Hurdle Drill and Leader Drill exercises was implemented to enhance muscle explosiveness, balance, agility, coordination, and step speed. Objectives. This study aims to analyze the effect of combined hurdle and leader drills on Dolyo Chagi kick speed in junior Taekwondo athletes. Methods. The research method used the One Group Pretest-Posttest experimental design. The training program lasted for 16 sessions in one month with four training sessions per week. Measurements were made by counting the number of kicks in 10 seconds, and the data were analyzed through descriptive analysis, prerequisite tests, and parametric tests. Results. The research results show a significant increase from 11.60 to 14.90 kicks in 10 seconds, with a statistically significant difference between the pretest and posttest (p < 0.05). In addition to the increase in speed, this training also improves foot movement coordination, body stability, and movement transition agility. Conclusion. Thus, the combination of Hurdle Drill and Ladder Drill effectively enhances the performance of the Dolyo Chagi kick and is recommended for the training of Taekwondo athletes. This study contributes to sports science by providing empirical evidence that agility-based drills can significantly improve kicking speed, coordination, and explosiveness in junior athletes. Furthermore, it offers a practical training model that coaches can adopt and adapt to optimize athlete performance in martial arts disciplines.